'Miners, Wake Up!' by Tom Mann, 1911 (1911)
1911 1880-1914 "'Miners, Wake Up!' by Tom Mann, 1911" [T0189.jpg], 1911, Bowman, Guy, Mann, Tom No. 8 in a series of pamphlets on syndicalism entitled 'The Industrial Syndicalist' which was edited by Tom Mann.